American Society of ExtraCorporeal Technology: Development of Standards and Guidelines for Pediatric and Congenital Perfusion Practice (2019). - Oldeen, Molly E.; Angona, Ronald E.; Hodge, Ashley; Klein, Tom (Journal of Extra-Corporeal Technology, 2020)
The development of standards and guidelines by professional societies offers clinicians guidance toward providing evidence-based care. The ultimate goals of standards and guidelines are to standardize care and improve patient safety and outcomes while also minimizing risk. The American Society of ExtraCorporeal Technology (AmSECT) currently offers perfusionists several clinical resources, primarily the Standards and Guidelines for Perfusion Practice; however, no document exists specific to pediatric perfusion. Historically, the development of a pediatric-specific document has been limited by available scientific evidence because of smaller patient populations, sample sizes, and variable techniques among congenital perfusionists. In the current setting of evolving clinical practices and increasingly complex cardiac operations, a subcommittee of pediatric perfusionists developed the Standards and Guidelines for Pediatric and Congenital Perfusion Practice. The development process included a comprehensive literature review for supporting evidence to justify new recommendations or updates to the existing AmSECT Adult Standards and Guidelines document. Multiple revisions incorporating feedback from the community led to a finalized document accepted by the AmSECT member and made available electronically in May 2019. The Standards and Guidelines for Pediatric and Congenital Perfusion Practice is an essential tool for pediatric perfusionists, serves as the backbone for institutionally based protocols, promotes improved decision-making, and identifies opportunities for future research and collaboration with other disciplines. The purpose of this article is to summarize the process of development, the content, and recommended utilization of AmSECT's Standards and Guidelines for Pediatric and Congenital Perfusion Practice. AmSECT recommends adoption of the Standards and Guidelines for Pediatric and Congenital Perfusion Practice to reduce practice variation and enhance clinical safety.